2018
DOI: 10.3390/ijerph15112534
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Characteristics of Particulate Matter in Subway Tunnels in Seoul, Korea

Abstract: Hazards related to particulate matter (PM) in subway systems necessitate improvement of the air quality. As a first step toward establishing a management strategy, we assessed the physicochemical characteristics of PM in a subway system in Seoul, South Korea. The mean mass of PM10 and PM2.5 concentrations (n = 13) were 213.7 ± 50.4 and 78.4 ± 8.8 µg/m3, with 86.0% and 85.9% of mass concentration. Chemical analysis using a thermal–optical elemental/organic carbon (EC–OC) analyzer, ion chromatography (IC), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 64 publications
1
23
2
Order By: Relevance
“…Our measurements and analyses reveal variable and, in places, very high PM 2:5 exposures of commuters and transit workers in the underground subway systems of northeastern U.S. cities. The most extreme exposure, identified in a subway station on the PATH system (serving NJ and NYC), was higher than the previously published values for any subway station in the world (Martins et al 2016;Moreno et al 2017;Qiu et al 2017;Van Ryswyk et al 2017;Xu and Hao 2017;Lee et al 2018;Minguillón et al 2018;Mohsen et al 2018;Moreno and de Miguel 2018;Choi et al 2019;Loxham and Nieuwenhuijsen 2019;Pan et al 2019;Shen and Gao 2019;Velasco et al 2019;Smith et al 2020), with a mean gravimetric PM 2:5 concentration greater than 1,000 lg=m 3 PM 2:5 ( Figure 1). The MTA-serviced subway stations in Manhattan also had poor air quality, with an adjusted real-time mean ± SD PM 2:5 concentration of 548 ± 207 lg=m 3 .…”
Section: Discussionmentioning
confidence: 54%
“…Our measurements and analyses reveal variable and, in places, very high PM 2:5 exposures of commuters and transit workers in the underground subway systems of northeastern U.S. cities. The most extreme exposure, identified in a subway station on the PATH system (serving NJ and NYC), was higher than the previously published values for any subway station in the world (Martins et al 2016;Moreno et al 2017;Qiu et al 2017;Van Ryswyk et al 2017;Xu and Hao 2017;Lee et al 2018;Minguillón et al 2018;Mohsen et al 2018;Moreno and de Miguel 2018;Choi et al 2019;Loxham and Nieuwenhuijsen 2019;Pan et al 2019;Shen and Gao 2019;Velasco et al 2019;Smith et al 2020), with a mean gravimetric PM 2:5 concentration greater than 1,000 lg=m 3 PM 2:5 ( Figure 1). The MTA-serviced subway stations in Manhattan also had poor air quality, with an adjusted real-time mean ± SD PM 2:5 concentration of 548 ± 207 lg=m 3 .…”
Section: Discussionmentioning
confidence: 54%
“…Thirdly, the crustal particles (mainly silicates) are not only from the mineral dust in infiltrated outdoor air but also from construction material and rock soil inside subways. Halite and secondary inorganic compounds like water-soluble nitrate, sulfate, and ammonium are rare in subway air and usually infiltrate from outside [80,98,110,111,121,137].…”
Section: Pmsmentioning
confidence: 99%
“…On the other hand, Zhu et al [14] showed that the condensed water film counteracts the hematite (α-Fe2O3) on the surface, which tends to decrease the coefficient of friction. However, White et al [12] showed that the coefficient of friction increased depending on the type of iron oxide in the wheel-rail contact.…”
Section: Discussionmentioning
confidence: 99%